THE INFLUENCE OF CORPORATE IMAGE, RISK PERCEPTION, AND TRUST ON LIFE INSURANCE PURCHASING DECISION (Case Study of Generali Insurance Pontianak) - admin, WILLY B12111015 (Jurnal Manajemen Update, 2017)
Abstract Â  Low insurance ownership in Indonesian society can be seen in terms of consumer behavior and family financial management. In this case the family financial planning in the purchase of insurance. Factors consumer perceptions of risks and benefits of the insurance products as well as access information about insurance is expected to affect financial planning in the purchase of insurance. Risk perception of a product or service consists of six components, namely economic, social, purchasing decisions (functional), psychological, physical, and time. This study aims to determine the effect of the corporate image of the insurance purchase decision; influence the perception of risk to insurance purchasing decisions; influence confidence in the insurance purchase decisions and influence corporate image to insurance purchasing decisions through risk perception and trust. This research was conducted at Generali Insurance branch Pontianak in West Kalimantan in December 2016. The location was chosen on the basis that the company is one of the companies operating company engaged in the marketing and sale of insurance products in West Kalimantan. The population from which the sample is Generali insurance customers who have invested in insurance products Generali as many as 100 people. Data were collected by interview based on a questionnaire. Based on the results of the research show that corporate image significantly affect and positive impact on Generali insurance purchase decision. Variable risk perception significant effect and positive impact on the variable insurance purchasing decisions. Trust significant effect and positive impact on the insurance purchasing decisions. Because the path coefficient is positive, it can be said that with the growing belief that a consumer will affect the high purchase insurance products. Variables in risk perception and trust indirect effect, positive and significant impact on the purchase decision variables Generali insurance through the corporate image with a value of 0.085. Because the coefficient is positive it can be said that with the increase of the corporate image will indirectly boost consumer trust and lower the perception of risk that will affect the high Generali insurance purchase. Â  Keywords: insurance, purchasing, corporate image, risk perceptions, trust